Pengaruh Earnings Management Terhadap Nilai Perusahaan Dimoderasi Dengan Praktik Corporate Governance - Ludwina Damei; Einde Evana; Yenni Agustina; Fajar Gustiawaty Dewi (Universitas Bandar Lampung (UBL), 2022)
Problems in the practice of corporate governance arise and occur because of differences and separation between control and ownership of the company. This study has a purpose, including to analyze the effect of Earning Management on firm worth, to investigate the impact of Corporate Governance on firm worth, and to dissect the benefits of Corporate Governance effect on firm worth and acquiring the executives. The populace taken in this study is organization information recorded on the IDX. Inspecting was done utilizing purposive examining strategy. The data used by the researcher includes secondary data, namely quantitative data obtained from the BEI website. The data collection method of this research is documentation data. The stages of data analysis were carried out through the stages of descriptive statistics, classical suspicion tests, and speculation testing. The outcomes showed that income the board had a critical adverse consequence on firm worth, institutional proprietorship as a directing variable of profit the executives on firm value had a significant positive effect, and the independent commissioner variable as moderating variable of earnings management on firm value had a significant positive effect